Kecerdasan Saja Tidak Cukup: Pentingnya Membangun Jiwa Nasionalisme pada Generasi Muda di Era Globalisasi dengan Pendidikan Pancasila - Maulani, Cindy; Firdaus, Muhamad Davin Akbar; Akbarkusumah, Muhammad Fadlan; Rachail, Meisya Siti; Septiani, Sephia; Zafira, Zil Sala; Furnamasari, Yayang Furi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
In the era of globalization, Indonesia's young generation faces challenges that erode the sense of nationalism and national values. Globalization, although it brings advances in information and communication technology, has also resulted in strong foreign cultural influences, reducing local values. This research aims to find out the importance of building the spirit of nationalism in the younger generation with Pancasila education. This study uses a literature study method by collecting data from various sources such as journal articles, books, and previous research reports. The main source of data for this research is the research article published through google scholar. The analysis stages are carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The findings of this study are that the Pancasila learning method must be adapted to the needs of the current young generation, with an interactive and technology-based approach. Family, school, and community play an important role in instilling nationalist values. Character education from the family, extracurricular activities in schools, and social programs in the community all contribute to the formation of national character. Mass media and information technology must also be used to foster the spirit of nationalism through educational and inspirational content